INTEGRATED PRACTICE LEARNING MODEL TO IMPROVE WAITER/S’ COMPETENCY ON HOSPITALITY STUDY PROGRAM, POLITEKNIK NEGERI BALI - I Made Darma Oka; I Ketut Sadia; I Wayan Pugra (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
Hospitality Study Program, Politeknik Negeri Bali (PNB), hadn’t implemented integrated learning practice optimally. The aim of this research was improving the learning process method as an integrated practice learning model involving three courses (Food Production, FB Service, English for Restaurant) in the same topic. This study was conducted on the forth semester of Hotel Study Program as the sample used in this research. After the random sampling was selected two classes as research samples, those were IVA class as an experiment group and IVB class as a control. Thus the samples could be determined according to the number of students in each class as many as 26 people. The application of integrated practice learning had an effect on the achievement of student competency in waiter/s occupation at Hotel Studies Program. The result of statistical test showed that there was a significant difference of competency achievement between integrated learning practices with partial practice learning students groups. It’s suggested to the management Hospitality Study Program to encourage and to facilitate the lecturers especially of core subjects to apply integrated learning practices in order to achieve the competency.